Disruptive Potential of the Internet to Transform Illicit Drug Markets and Impact on Future Patterns of Drug Consumption. Issue 2 (20th December 2016) - Griffiths, P; Mounteney, J
Abstract : The internet facilitates rapid and covert communication, knowledge transfer, and has the potential to disrupt and transform drug market models and associated consumption patterns. Innovation and new trends diffuse rapidly through this medium and new operational models are emerging. Although the online drug markets currently only account for a small share of all drug transactions, the potential of the surface and deep web to provide a new platform for drug sale and exchanges is considerable.